Narcissism and Cultural Liberation: A Textual and Cultural Analysis of Carol Shields’ ‘Mirrors.’ - Good, Rebecca (Université d'Ottawa | University of Ottawa, 2018)
This paper will analyze Carol Shields‘ short story "Mirrors" in the collection Dressing Up for the Carnival. The paper will explore how the absence of mirrors in the story creates a break in narcissism, which liberates the characters from cultural impositions. This will be done using Jonathan Culler‘s ―Narrative‖ to analyze the parts of the plot where mirrors appear, or where the couple mirrors each other. The analysis will utilize the psychoanalytical and cultural underpinnings of Freud, Lacan, Lunbeck, Friedman, and Adorno and Horkheimer. Through the breaks in narcissism, the characters are liberated from the cultural impositions of vanity, fashion, marriage, and beauty, among others. Finally, the aspects of narcissism inherent in the setting and internal dialogue of the characters will be examined.
Keywords: Carol Shields; mirrors; identity; culture; narcissism